2008
DOI: 10.1007/s10803-007-0512-z
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress in Mothers and Fathers of Toddlers with Autism Spectrum Disorders: Associations with Child Characteristics

Abstract: Elevated parenting stress is observed among mothers of older children with autism spectrum disorders (ASD), but little is known about parents of young newly-diagnosed children. Associations between child behavior and parenting stress were examined in mothers and fathers of 54 toddlers with ASD (mean age = 26.9 months). Parents reported elevated parenting stress. Deficits/delays in children's social relatedness were associated with overall parenting stress, parent-child relationship problems, and distress for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

57
611
11
38

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 925 publications
(717 citation statements)
references
References 41 publications
57
611
11
38
Order By: Relevance
“…Sometimes mothers also reported marital strain because of conflicts about their child's upbringing. In line with the evidence of parents' strengths and resilience in coping with the diagnosis of ASD, as found in past studies (Bayat, 2007;Davis & Carter, 2008;Phelps et al, 2009), the mothers in our study also have shown to do 'all they can' for their child with ASD. However, in spite of this, many of mothers' questions and concerns remained unanswered.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Sometimes mothers also reported marital strain because of conflicts about their child's upbringing. In line with the evidence of parents' strengths and resilience in coping with the diagnosis of ASD, as found in past studies (Bayat, 2007;Davis & Carter, 2008;Phelps et al, 2009), the mothers in our study also have shown to do 'all they can' for their child with ASD. However, in spite of this, many of mothers' questions and concerns remained unanswered.…”
Section: Discussionsupporting
confidence: 91%
“…The children's restricted social, communicative and emotional competencies, their uneven cognitive development, and their maladaptive behaviour place tremendous stress on parents of children with ASD (Davis & Carter, 2008;Hastings & Johnson, 2001). In comparison to mothers of typically developing (TD) children and mothers of children with other disabilities, mothers of children with ASD report elevated stress levels (Eisenhower, Baker, & Blacher, 2005;Estes, et al, 2009;Montes & Halterman, 2007;Rao & Beidel, 2009) and they are at an increased risk for depression (Olsson & Hwang, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is notable that neither adolescent intellectual functioning (as measured by scores on the KBIT-2) nor ASD symptomology (as measured by total score on the ADOS-G) were associated with parenting stress, parenting self-efficacy, or family chaos. This finding replicates earlier research which demonstrated no difference in parenting stress for parents of children with or without cognitive deficits (Davis and Carter 2008;Rao and Beidel 2009) or for parents of children with varying severity of social and communicative impairment (Tomanik et al 2004). The fact that parenting stress and self-efficacy do not appear related to these domains of child functioning highlights the need for parent involvement in treatment even when teens are classified as "higher-functioning," as was the case in the present study.…”
supporting
confidence: 90%
“…13 Conversely, evidence suggests that parental behavior may affect the prognosis of autism from the child's early years until adulthood. [14][15][16] Within this perspective, in order to improve understanding of the eating behavior of the child with ASD, not only the specificities of ASD must be taken into consideration, but also the parents' behavior in relation to the child's dietary restrictions. The present qualitative study investigated the eating behavior of autistic individuals through their mothers' narratives, and also collected information on the family's eating behavior and how the family deals with the child's eating restrictions.…”
Section: Introductionmentioning
confidence: 99%